Enhancing Human Capital Management through DevOps Practices - Bayu Dwi Suharminto; Alek Wijaya; Tata Sutabri; Ahmad Syazili (LPPM Universitas Islam 45 Bekasi, 2024)
In the current era of digital revolution, one of the main factors influencing an organization's performance is human resources. This is because HR is an important asset that determines the productivity and efficiency of organizational performance. This study's goal is to create and construct an integrated human resources application using the DevOps (Development and Operations) approach. The DevOps method is a collabo rative approach that combines the process of software development and operations in a sustainable, fast, and integrated manner. The human resources application developed in this research includes various important functions, including HR management, job grade promotion planning, employment contract termination notification, and promotion notification. This research also provides solutions to the problems experienced by the Palembang Region Office of PT Bank Rakyat Indonesia in human resource management. By using the DevOps method as a method of designing human capital applications, it is expected to increase employee efficiency and productivity through integrated and effective human resource management. The DevOps approach also allows organizations to respond quickly to changing needs and provide sustainable added value to the organization.